Pengaruh Fire Proofing pada Balok Beton Pasca Bakar - Sudibyo, Gathot Heri; Setyo H., Nor Intang (Dinamika Rekayasa, 2010)
Problem of buildingfire, which is often happened, cannot be avoided. Burning that happened generally reach temperature of above 200oC, what of course influence concrete strength. Concrete material will become brittle, spelling, and barest easyto and its strength is downhill effect of high temperature. In this research the specimens are cylinder shape of concrete and reinforced concrete beams. For this type of concrete cylinder specimens were made with size of 15 cm diameter and 30 cm high, while for the typeof reinforcedconcrete beam specimens were made with size of 15 cm x 20 cm x 150 cm. Each type of specimen for each variety is made of 3 repetitions. Variations in temperature used are normal temperatures, 400o C, 600o C and 800o C.The results of research show that the use of fire proofing provide the value of concrete compressive strength better than the concrete without fire proofing.The fire proofing increased the compressive strength by 2.50%, 5.70% and 11.89% for temperature of 400o C, 600o C and 800o C respectively. While the influence of fire proofing on the flexural strength of reinforced concrete beams at the respective temperatures are 4.99%, 23.97% and 20.55%.